Access to medicines for children in China. Issue 1 (15th December 2022) - Chen, Zhe; Li, Siyu; Choonara, Imti; Zou, Kun; Zeng, Linan; Huang, Liang; Jia, Zhi-Jun; Cheng, Guo; Jiang, Yongmu; Tang, Yong; Zhao, Shaoyang; Zhang, Lingli
Abstract : Access to essential medicines for children is a big challenge, particularly in low-income and middle-income countries. In China, the average availability of essential medicines for children is 1.6%–46.5%. The availability of generics was generally higher than original brands in public hospitals and the prices of generics were relatively lower and more reasonable (generics: availability, 27.3%–46.5%, prices, 0.52–4.28 times the international reference prices; original brands: 1.6%–33.0%, 2.59–11.38 times the international reference prices). In terms of affordability of medicines for children, generics were more affordable than original brands and tablets/capsules were more affordable than injections. Most commonly used anti-infective medicines (such as amoxicillin capsule, azithromycin tablet, cefuroxime tablet) and antipyretics (such as ibuprofen suspension) were relatively affordable. Six commonly used medicines in paediatrics, including amoxicillin/clavulanic acid, beclomethasone, cefazolin, ceftazidime, ceftriaxone, cyclosporine were unaffordable. Since August 2011, China has successively issued several policies to ensure the accessibility of medicines for children, covering research and development, production, procurement and prices of medicines. The accessibility of medicines for children has been partially improved, but still needs continuous improvement.